HISTORY OF ENGLISH WRITING DOCUMENTS IN THE MIDDLE AGES - Nasimova Sohiba Yakhyaevna (Research Focus International Scientific Journal, 2023)
This article represents history of writing In the Middle Ages. On that time, they only the educated elite could read and write. Nevertheless, the English government and legal system relied on written evidence. Many of the surviving medieval documents record the acquisition of land, the resolution of disputes, the payment of money, and the rights and responsibilities of individual people: things, which it was important for people to know and prove. Other documents record the cultural life of the Middle Ages. Bibles, prayer books, service books and works of pious instruction remind us of the central role of the Catholic Church. However, many literary works are secular, and intended for entertainment. Until the invention of the printing press in the fourteenth century everything was hand-written.